Sulfur dioxide exploitation by electrochemical oxidation of sulfite in near-neutral pH electrolytes: A kinetics and mechanistic study - R.A. Márquez-Montes; R.E. Orozco-Mena; D. Lardizábal-Gutiérrez; D. Chávez-Flores; A. López-Ortíz; V.H. Ramos-Sánchez (Electrochemistry Communications, 2019)
Electrochemical oxidation of sulfite ions offers an efficient and profitable approach to the conversion of sulfur dioxide, a harmful air pollutant, into valuable by-products via flue gas desulfurization. Here, the electrochemical oxidation of sulfite in near-neutral pH electrolytes is studied in order to determine kinetic parameters and a reaction mechanism. Sulfite electrooxidation on palladium is demonstrated at pH 7.5 and 8.5, the latter being comparable to platinum. Anodic charge transfer coefficients and non-linear reaction orders are linked to a mechanism which involves sulfite adsorption at low potentials. This study proves that sulfite electrooxidation on palladium at near-neutral pH is a useful approach for sulfur dioxide exploitation. Keywords: Sulfite electrooxidation, Kinetics, Palladium, Reaction mechanism